Удосконалення якості готельно-ресторанних послуг - Роженюк, Дмитро Олександрович; Rozhenyuk, Dmytro Oleksandrovych (Ірпінь, 2024)
В даній кваліфікаційні роботі визначено особливості управління якістю готельно-ресторанних послуг; досліджено загальну характеристику та особливості діяльності магазину з кафетерієм «ФОП Роженюк О.М.»; визначено проблеми та запропонувано напрями удосконалення якості готельно-ресторанних послуг.

This qualification paper defines the features of hotel and restaurant quality management services; the general characteristics and specifics of the activity of the shop with a cafeteria "FOP Rozhenyuk O.M." were investigated; problems are identified and directions for improvement are proposed quality of hotel and restaurant services.
Improving the quality of hotel and restaurant services
Keywords: готельно-ресторанна сфера; послуги; якість послуг; управління; hotel and restaurant industry; services; quality of services; management